Grab: Building a leading O2O technology company in Southeast Asia - SMITH, Richard Raymond (Institutional Knowledge at Singapore Management University, 2019)
The case is set the day after Grab Holdings (“Grab”) announced the acquisition of its largest rival, Uber, on 26 March 2018, and traces back its evolution from a start-up struggling to gain traction in its target market to the region’s first decacorn (start-up with $10 billion or more value). Within five years since its inception in 2012, Grab had established a wide-spanning footprint in 190 cities across eight countries of Southeast Asia. To keep pace with its growth, the company had moved its headquarters to Singapore in 2014. Commencing its debut in the Online-to-Offline (O2O) market with a prototype of its taxi-booking smartphone app in the company’s hometown in Malaysia, Grab has come a long way. With its extensive range of personal transport service, the company has become synonymous with ride-hailing and has also forayed into other areas such as fintech and marketplace. Appropriately, in January 2016, the company rebranded itself to ‘Grab’, an umbrella under which all its services are now homed. When Uber, the US behemoth, flexed its muscles and posed a severe threat, Grab fought head-to-head and won over the giant by quickly altering its business model and adopting a hyper-local approach. Grab’s focus on nurturing a congenial organisational culture, disruptive innovation, customer-centric services, and agility while fostering enterprising and innovative talent has helped to defend its position. While staying steady on its high-growth trajectory, Anthony Tan and Hooi Ling Tan, the founding CEO and the founding COO, respectively, want to fortify its competitive strength by enhancing its disruptive quotient while remaining entrenched in Grab’s culture. How can they best go about doing so?